Cytotoxicity of chitosan hydrogels aginst L929 cells - Adrianna Banach-Kopeć; Joanna Pilch; Szymon Mania; Ewa Augustin; Robert Tylingo (Gdańsk University of Technology, 2021)
This study presents absorbance values of formazan product (converted from MTT) which corresponds to the cytotoxicity of chitosan compounds (dissolved in carbonic acid, dissolved in carbonic acid endotoxin free, and dissolved in hydroxyacetic acid) aginst adult mouse fibroblast L929 cells. The experiments were carried out according to the ISO 10993-5:2009(E) standard. Cytotoxicity of compounds was measured in three different dilution factors: 1:1; 1:3 and 1:6. Briefly, L929 cells were seeded at 104 per well. After 24 h of incubation, the medium was replaced with new medium containing compounds and incubated for 24 h. Following 24 h of the treatment, the medium was changed to fresh containing 1 mg/mL MTT and incubated for 2 h. Next, the medium was removed and formazan crystals were dissolved in 100 µL of isopropanol. The absorbance was measured using a spectrophotometer (540 nm). Based on the results % of viability was determined, assuming that the control was 100%.